Correlation of serum adipocytokine levels with glycolipid metabolism and inflammatory factors in obese patients with periodontal disease - Li, Zejian (Int J Clin Exp Pathol, 2018)
Objective: To analyze the correlation of serum levels of visfatin, leptin, resistin, and adiponectin (APN) with glycolipid metabolism and inflammatory factors in obese patients with periodontal disease. Methods: 116 obese adults (OB), of whom 78 participants were diagnosed with different degrees of chronic periodontitis (CP), and 50 healthy adults were recruited into the study. Fasting peripheral venous blood was extracted to determine serum levels of adipocytokines (e.g., visfatin, leptin, resistin, and APN), glucolipid metabolism (e.g., fasting blood glucose (FBG), fasting insulin (FINS), C-peptide (C-P), cortisol (Cor), homeostasis model of assessment for insulin resistance index (HOMA-IR), glycosylated hemoglobin (HbA1c), triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and non-high-density lipoprotein cholesterol (non-HDL)), and micro-inflammation-related indexes like C-reactive protein (CRP), interleukin (IL)-1β, IL-6, IL-10, and tumor necrosis factor (TNF)-α. Correlation between levels of adipocytokines and levels of glucolipid metabolism and inflammatory factors was further analyzed. Results: Assays for plasma levels of adipocytokines showed that both the OB group and the OB with CP group had significantly higher serum levels of visfatin, leptin, and resistin than the normal control group and significantly lower serum levels of ANP than the normal control group (P<0.05). Detection of serum glucolipid metabolism levels showed that FBG, FINS, C-P, Cor, HOMA-IR, TG, TC, LDL-C, HDL-C, Non-HDL-C of OB group, and OB with CP patients were significantly higher than those of normal patients (P<0.05). Assay for plasma levels of inflammatory factors showed that both the OB group and the OB with CP group had significantly higher serum levels of CRP, IL-1β, IL-6, and TNF-α than the normal control group and significantly lower serum levels of IL-10 than the normal control group. Spearman’s correlation analysis revealed that serum levels of visfatin, leptin, resistin, and APN were significantly correlated with concentrations of FBG, FINS, C-P, Cor, TG, TC, LDL-C, HDL-C, Non-HDL-C, CRP, IL-1β, IL-6, IL-10, and TNF-α. Conclusions: There were high expression levels of inflammatory factors and glucolipid metabolism disorder in obese patients with periodontal disease and excessively expressed adipocytokines may be important factors of persistent and worsened obesity and of periodontitis.